Global sourcing and corporate social responsibility: analyzing how global companies control social responsibility in its suppliers - Longo, Júlia Melânia (My University, 2021)
This study develops an analysis around global sourcing strategies and corporate social responsibility, strictly how global companies control corporate social responsibility in their international suppliers. To this end, knowledge was sought in the areas of global strategies, corporate social responsibility, and initiatives of global organizations focused on sustainable development. The main purpose of this study is to observe how global companies control corporate social responsibility in their international suppliers. This research is qualitative exploratory, and the method chosen for data collection is semi-structured interviews. The respondents were selected by collusion, being executives from the purchasing area of six companies from Serra Gaúcha. From this, it was concluded that these global companies control their suppliers by evaluating certificates and making recurring visits. It was also concluded that corporate social responsibility influences investors in publicly and privately held companies, thus becoming an indispensable initiative nowadays. [resumo fornecido pelo autor]
O presente estudo desenvolve uma análise em torno de estratégias de fornecimento global e responsabilidade social corporativa, estritamente como empresas globais controlam responsabilidade social corporativa em seus fornecedores internacionais. Para tanto, buscou-se conhecimento nas áreas de estratégias globais, responsabilidade social corporativa e iniciativas de organizações mundiais voltadas ao desenvolvimento sustentável. Este estudo tem como objetivo principal observar como empresas globais controlam a responsabilidade social corporativa em seus fornecedores internacionais. Esta pesquisa é qualitativa exploratória e o método escolhido para a coleta de dados é entrevista semiestruturadas. Os entrevistados foram selecionados por conivência, se tratando de executivos da área de compras de seis empresas da Serra Gaúcha. A partir disso, chegou-se à conclusão de que estas empresas globais fazem o controle em seus fornecedores avaliando certificados e fazendo visitas recorrentes. Também se conclui que responsabilidade social corporativa influência investidores de empresas de capital aberto e fechado, tornando-se assim uma iniciativa indispensável nos dias de hoje. [resumo fornecido pelo autor]
Keywords: Comércio internacional; Responsabilidade social da empresa; Sustentabilidade; Empresas - Aspectos sociais